2022
DOI: 10.5336/caserep.2022-91268
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol-Induced Anaphylaxis: A Rare Case

Abstract: Tramadol hydrochloride is used to treat acute and chronic pain of moderate intensity. 1 It is generally considered a safe analgesic. The incidence of allergic reactions is less than 0.1%. 2 According to the World Allergy Organization (WAO), anaphylaxis is a severe systemic hypersensitivity reaction that usually starts quickly and can cause death. Severe anaphylaxis is a potentially lifethreatening condition in the airway, respiratory, and circulation. Food products, insect bites, and drugs are the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…A low frequency of anaphylaxis is also known for benzodiazepines [ 61 ], though diazepam is considered to be a more common cause of allergy compared with midazolam [ 62 ]. Pagani et al (2022) indicated a frequency of anaphylaxis due to tramadol equal to 0.32%, 2/608 [ 17 ], and a literature analysis revealed only a few cases of tramadol-induced anaphylaxis [ 63 , 64 , 65 ]. Conversely, some studies based on analyses of pharmacovigilance databases reveal a significant role for several drugs affecting CNS.…”
Section: Discussionmentioning
confidence: 99%
“…A low frequency of anaphylaxis is also known for benzodiazepines [ 61 ], though diazepam is considered to be a more common cause of allergy compared with midazolam [ 62 ]. Pagani et al (2022) indicated a frequency of anaphylaxis due to tramadol equal to 0.32%, 2/608 [ 17 ], and a literature analysis revealed only a few cases of tramadol-induced anaphylaxis [ 63 , 64 , 65 ]. Conversely, some studies based on analyses of pharmacovigilance databases reveal a significant role for several drugs affecting CNS.…”
Section: Discussionmentioning
confidence: 99%